Penerapan Manajemen Kinerja Sekolah dalam Peningkatan Mutu Pendidikan di SMA PAB 4 Sampali - Khairani Berutu; Inom Nasution; Zulkifli Tanjung (Jurnal Manajemen dan Pendidikan Agama Islam, 2024)
The research that has been carried out is entitled "Implementation of School Performance Management in Improving the Quality of Education at SMA PAB 4 Sampali". This research aims to: Find out how school performance management is implemented in improving the quality of education, find out the steps in implementing school performance management in improving the quality of education. To obtain data in this research, the author used qualitative research methods from data produced through observation, interviews and documentation. The data analysis used was data reduction, data presentation, and drawing conclusions. This research was carried out in the principal's room and the teacher's room. From the results of research at this school, it can be concluded that SMA PAB 4 Sampali has implemented part of the process of implementing school performance management in improving the quality of education. In implementing school performance management there are inhibiting and supporting factors in this education. And activities for implementing school performance management have running well, but not yet fully implemented, because the school principal has not held regular meetings to evaluate the program of activities that have been planned and implemented so that the implementation of school performance management in improving the quality of education runs well.